If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 3 = -11 Reorder the terms: 3 + 2a = -11 Solving 3 + 2a = -11 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2a = -11 + -3 Combine like terms: 3 + -3 = 0 0 + 2a = -11 + -3 2a = -11 + -3 Combine like terms: -11 + -3 = -14 2a = -14 Divide each side by '2'. a = -7 Simplifying a = -7
| 15+8-12=x | | 12x+2=3x+11 | | 16x-18+6x+4=118 | | 32+8v=8(7v-2) | | -8=23-5q | | f(x)=5x^2-7x^3 | | -3-6x^2=-103 | | 1+6p=1-p | | 5+a=29 | | (11t-s)(t+5s)= | | -10x+2=-10 | | -10x+2=-11 | | -12=8+f2 | | 14000=36000-1500t | | 1400=36000-1500t | | -20=-5n+-3n | | 35=1-2a | | -41=2x-7 | | -5(6y-9)-y=-2(y-4) | | 4(x-3)=6(x+1) | | -2(5x-1)=11 | | n^2+5=105 | | -7x+24=8+x | | (2b-5)(2b+5)= | | -3-8(3-2k)=-155 | | -2x^2=-76 | | 2.5(+-2)-6=9 | | 5x-5(2-2x)=-10 | | x-5+4=9 | | 2-6x=10-2x | | 10x+24(x-3)=336 | | 25-15+14=x |